2021
DOI: 10.1007/s12571-020-01140-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact that cultural food security has on identity and well-being in the second-generation U.S. American minority college students

Abstract: Food contributes to an individual's physical and mental well-being and expresses one's cultural identity through preparation, sharing, and consumption (i.e., foodways). Inadequate access to cultural foods can create cultural stress and affect one's identity and well-being. In particular, second-generation U.S. American student populations may have a higher risk for cultural stress due to being away from family, academic stress, environmental changes, and diminished financial stability to purchase cultural food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Using the photovoice method, the present study aims at exploring undergraduate nursing and medical students’ perceptions of food security and the circumstances that affect their access to healthy food in Qatar. Many studies have found associations between food security and diet-related outcomes, including academic performance ( 28 ) , diet quality ( 29 ) , food literacy and integrating food courses into the curriculum for nursing students ( 30 , 31 ) , effect of the COVID-19 pandemic ( 32 ) and the impact of cultural food on the identity and well-being of undergraduate students ( 33 ) . The results of the current study assist in exploring these aspects by understanding how undergraduate nursing and medical students experience food security, their access to healthy food in Qatar and the various circumstances that affect their access to healthy food.…”
Section: Discussionmentioning
confidence: 99%
“…Using the photovoice method, the present study aims at exploring undergraduate nursing and medical students’ perceptions of food security and the circumstances that affect their access to healthy food in Qatar. Many studies have found associations between food security and diet-related outcomes, including academic performance ( 28 ) , diet quality ( 29 ) , food literacy and integrating food courses into the curriculum for nursing students ( 30 , 31 ) , effect of the COVID-19 pandemic ( 32 ) and the impact of cultural food on the identity and well-being of undergraduate students ( 33 ) . The results of the current study assist in exploring these aspects by understanding how undergraduate nursing and medical students experience food security, their access to healthy food in Qatar and the various circumstances that affect their access to healthy food.…”
Section: Discussionmentioning
confidence: 99%
“…College students, as the new force of the country, should cultivate their aesthetic and innovation abilities. Reading art journals might shed light on college art education reform by improving their national cognition and cultural acceptance ( Wright et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity, defined broadly as the unreliable availability, use, stability and access to sufficient, culturally safe and nutritious food, is a widespread global problem with considerable health effects 13–15. As evidence from Canada and other popular immigrant-destination countries continues to accumulate,5 16–20 food insecurity among postsecondary students has been brought to the centre of policy and scholarly discussions. According to a survey on food insecurity among postsecondary students at five Canadian universities, about 39% of students experienced some level of food insecurity 21.…”
Section: Introductionmentioning
confidence: 99%
“…In another review that focused exclusively on college students in the USA, the prevalence rate ranged from 10% to 75% 23. Food insecurity is more common among ethnic minority students because they are more likely to experience structural barriers to getting foods that meet their cultural food needs 18 19 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation